Pain in Older Adults: Epidemiology, Impact and Barriers to Management - Schofield, Pat (Rev Pain, 2007)
There will be increased numbers of older adults in society in the next few decades. Older adults are more likely to have pain problems and other co-morbidities. Generally pain is poorly managed in older adults and this becomes worse when cognitive impairment exists. The impact of chronic pain on older adults will be greater than that of their younger counterparts in terms of social isolation. Attitudes and barriers exist in both the older adults themselves and their younger counterparts.